Analisis Kesalahan Peserta Didik dengan Gaya Kognitif Field Independent dalam Menyelesaikan Soal Cerita SPLTV - Zumrotul Auliya; Lestariningsih Lestariningsih (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2020)
The purpose of this research is to describe the results of the error analysis of students with a field-independent cognitive style in solving word problems about a system of linear equations with three variables. This research used a qualitative descriptive study. Determining the subject based on acquisition test results about the GEFT were awarded to 36 students to differentiate types of cognitive styles of learners and the acquisition of the problems and the causes of errors natural completing word problems. The subjects used in this research were 2 students who had a field-independent cognitive style with 13 to 15 GEFT test scores and had the SPLTV story question completion results which researchers considered to have errors that needed to be discussed in this research. The research result showed the location of the error encountered in modeling the context of a given story problem. Besides, the type of error committed in calculating with the appropriate method. Meanwhile, the factors causing the errors found were students' lack of understanding in the context of the questions.